Implementation of the Semantic Mapping Strategy for Teaching Reading Comprehension - Usman Kasim; Sri Wahyuni (Universitas Syiah Kuala, 2016)
This research studies the implementation of Semantic Mapping Strategy (SMS) in teaching reading comprehension to second year students from a junior high school in Aceh Besar. The objectives were to find out whether students taught reading comprehension through SMS would get better results than those who were taught using the Grammar Translation Method (GTM), the types of reading sub-skills that they would master better by using the SMS, and their responses towards the use of the SMS in reading comprehension classes. The sample for this research was two classes, one as the control group (CG) and another as the experimental group (EG). The classes were selected using a random sampling technique. The research instruments used to collect the data for this research were reading comprehension tests (pre-tests and post-tests) and a questionnaire. The result of this research showed that the students in the EG who were taught reading comprehension using the SMS got better results than the students in the CG who were taught using the GTM. Furthermore, the reading sub-skills where the students got better results through using SMS were ‘main idea’, and ‘specific information’. Finally, the students responded positively to the implementation of SMS in their reading comprehension classes. Thus, it can be said that the SMS was proven an effective strategy to be used for teaching reading comprehension to the second year students of the school.